Global trends in the development of the world wine sector (Economics and region, 2024)
The wine industry plays a significant role in the global economy, being an important source of revenue for many countries. Wine is not only a commodity, but also an important export item that brings billions of dollars to the budgets of wine-producing regions. Major wine-producing countries such as France, Italy, Spain and the United States support a huge number of jobs in agriculture, manufacturing, logistics and tourism. Globalisation is having a significant impact on the development of the wine market, expanding opportunities for international trade and cultural exchange. Thanks to open markets and lower trade barriers, wines from different parts of the world are becoming available to a wider audience. However, growing competition and global quality standards create additional pressure on producers, forcing them to adapt to the requirements of the global market. The article is devoted to the analysis of global trends in the development of the wine industry in the world. The author analyses the dynamics of grape (fresh) and wine production in the world in 2000-2023; the area of vineyards; the structure of world wine production (without juice and must) in 2023; the dynamics of world wine consumption in 2000-2023; indicators of world wine exports and imports in 2023 by quantitative and cost criteria. The main leading countries in wine production are France, Italy and Spain, which traditionally hold leading positions in the global market due to centuries-old winemaking traditions, a variety of varieties and high quality products. In addition to these traditional leaders, new wine regions such as the United States (California), Australia, Chile and Argentina are actively developing their own production, which is increasing their share of the global market. The analysed data indicate a general downward trend in wine production and consumption, driven by both climatic conditions and the ‘echo’ of the COVID-19 pandemic, global changes in food demand and a decline in the purchasing power of the population in most regions. It is determined that the demand for wine will continue to grow, but this growth will be uneven depending on the region and type of wine. The article highlights the growing popularity of organic and ecological wines as consumers increasingly pay attention to sustainability and product quality.
Keywords: winemaking; viticulture; wine market; strategy; trade; globalisation